Defining the role of NK cells during dengue virus infection. Issue 4 (17th April 2018) - Mathew, Anuja
Summary: In recent years, our understanding of the complex number of signals that need to be integrated between a diverse number of receptors present on natural killer (NK) cells and ligands present on target cells has improved. Here, we review the progress made in identifying interactions between dengue viral peptides presented on HLA Class 1 molecules with inhibitory and activating killer‐like immunoglobulin receptors on NK cells, direct interactions of viral proteins with NK cell receptors, the involvement of dengue virus‐specific antibodies in mediating antibody‐dependent cell‐mediated cytotoxicity and the role of soluble factors in modulating NK cell responses. We discuss findings of NK cell activation early after natural dengue infection, and point to the role that NK cells may play in regulating both innate and adaptive immune responses, in the context of our new appreciation of interactions of dengue virus with specific NK cell receptors. With a number of flavivirus vaccine candidates in clinical trials, how NK cells respond to attenuated dengue virus and subunit protein vaccine candidates and shape adaptive immunity will need to be considered. Abstract : Interactions between inhibitory and activating receptors on NK cells with dengue viral proteins and peptides.